Cigarette Use, E-Cigarette Use, and Dual Product Use Are Higher Among Adults With Serious Psychological Distress in the United States: 2014–2017. Issue 10 (13th April 2020) - Weinberger, Andrea H; Zhu, Jiaqi; Barrington-Trimis, Jessica L; Wyka, Katarzyna; Goodwin, Renee D
Abstract: Introduction: Cigarette use is declining yet remains common among adults with mental health conditions. In contrast, e-cigarette use may be on the rise. This study investigated the relationship between serious psychological distress (SPD) and the exclusive and dual use of cigarettes and e-cigarettes among US adults from 2014 to 2017. Aims and Methods: Data came from 2014 to 2017 National Health Interview Survey, an annual, cross-sectional survey of nationally representative samples of US adults (total combined analytic sample n = 125 302). Past-month SPD was assessed using the Kessler Psychological Distress Scale (K6) and cigarette and e-cigarette use were assessed at each wave. Logistic regressions examined product use by SPD status in 2017 and trends in product use by SPD status from 2014 to 2017. Analyses adjusted for demographic covariates. Results: The prevalence of cigarette use, e-cigarette use, and dual use was higher among adults with SPD than without SPD in each year including the most recent data year 2017 (cigarette use, 39.50% vs. 13.40%, p < .001; e-cigarette use, 7.41% vs. 2.65%, p < .001; dual use, 5.30% vs. 1.26%, p < .001). Among adults with SPD, the prevalence of cigarette, e-cigarette, and dual product use did not change from 2014 to 2017 in contrast to a decreasing prevalence in cigarette, e-cigarette, and dual product use among individuals without SPD. Conclusions: US adults with SPD report higher levels of cigarette, e-cigarette, and dual product use than adults without SPD. Use of these products has not declined over the past several years in contrast to decreasing trends among adults without SPD. Implications: These data extend our knowledge of tobacco product use and mental health disparities by showing that in addition to higher levels of cigarette use, US adults with SPD also use e-cigarettes and dual products (cigarette and e-cigarette) more commonly than those without SPD. Furthermore, the use of these products has not declined over the past several years in contrast to continuing declines among adults without SPD. More research is needed to understand the potential positive and negative consequences of e-cigarette use among adults with SPD.